IMPROVING STUDENTS RECOUNT TEXT WRITING BY USING TRAVEL MAP - Septy, Ferdina Eka; Bunau, Eusabinus; ., Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research is held to improve the studentsability in writing recount text, especially in organizing ideasthroughTravel Map as media. It is a Classroom Action Research which is conducted in three cycles. The subject of this research is Grade VIII, numbering 39 students. The data is collected by using observation checklist, fieldnote, and test. The data is analyzed by describing the observation checklist and fieldnote, and by using formula of mean score. The results indicate the studentswriting ability in recount text improve in three cycles through Travel Map as media. Key words: Writing,Travel Map, Recount Text Abstrak: Penelitian ini dilaksanakan untuk meningkatkan kemampuan siswa dalam menulis teks recount, khususnya dalam mengorganisir ide melalui Travel Map (peta perjalanan) sebagai media. Penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam tiga siklus. Subjek dari penelitian ini adalah Kelas VIII, yang berjumlah 39 siswa. Data penelitian dikumpulkan melalui ceklis observasi, catatan lapangan, dan tes. Data tersebut dianalisa dengan mendeskripsikan ceklis observasi dan catatan lapangan, dan menggunakan rumus mencari nilai rata-rata. Hasil penelitian menunjukkan kemampuan siswa dalam menulis teks recount meningkat dalam 3 siklus melaluiTravel Map (peta perjalanan) sebagai media. Kata kunci: Menulis, Peta Perjalanan, TeksRecount